PENGARUH LDR, CAR DAN NPL TERHADAP PROFITABILITAS BANK SWASTA DEVISA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Tantowi, Riki; Simanjuntak, Jontro (LPPM Universitas Putera Batam, 2021)
This research was conducted with the aim to empirically determine the effect of the LDR, CAR and NPL on ROA at private foreign exchange banks listed on the IDX. In addition, this study also empirically examines the effect of LDR, CAR and NPL on ROA simultaneously at private foreign exchange banks listed on the IDX. This research uses quantitative research methods with the type of causality research. The population was 30 and the sample amounted to 27 with a study period of 4 years from 2016 to 2019. The sample selection technique used the purposive sampling method. The data analysis method used in this study is multiple linear regression analysis, the statistical test consists of the t-test to test partially and the F-test to test simultaneously. The classical assumption test consists of the normality, multicollinearity, autocorrelation and heteroscedasticity test. The t-test results indicate that the LDR has no significant effect on ROA. Meanwhile, CAR and NPL have a significant effect on ROA. The results of the F test conclude that the LDR, CAR and NPL simultaneously have a significant effect on ROA. The R2 test results show that the LDR, CAR and NPL variables affect ROA by 28.5%.